Profil produktivitas belajar peserta didik sekolah dasar dalam ekosistem pembelajaran kolaboratif - Wiraman, Mahdum; Karsono, Karsono; Adi, Fadhil Purnama (Didaktika Dwija Indria, 2023)
Collaboration is one of the 4C skills needed for the development of learning to respond to the interests of students' adaptation to the 21st-century environment. One aspect of collaboration that can be reviewed in learning using problem-based learning in groups is the aspect of working productively. This study describes the aspects of working productively in collaboration skills in class VI students of SD Negeri Setono using Greenstein's perspective, especially in problem-based learning. This research is a type of research with a descriptive qualitative approach. The subjects of this study were students and teachers of class VI at SD Negeri Setono Surakarta. Collection techniques in this study were observation, interviews, questionnaires, and documentation studies. The Data validity testing technique uses technique and source triangulation. The collected data were then analyzed using the interactive data analysis technique of the Miles and Huberman model. The results of this study indicate that students can work productively in problem-based learning designed in groups. This can be seen from the emergence of all aspects of indicators of working productively in learning activities. The productivity shown by students is supported by other aspects of collaboration skills.